SAPHO SYNDROME: MISDIAGNOSED AND OPERATED - (:unkn) unknown (PUBLISAUDE-EDICOES MEDICAS LDA, 2008)
SAPHO is a rare disorder that results in synovitis, acne, pustulosis, hyperostosis and osteitis. Patients with this syndrome typically present with musculoskeletal complaints, frequently localized to the anterior chest wall. However, diagnosis can be difficult in case of involvement of only one symptomatic bone without skin lesions. Awareness of SAPHO syndrome is necessary for accurate diagnosis and to prevent inappropriate and unnecessary treatment.
Keywords: SAPHO Syndrome; Mediastinal Fibrosis; Sweet's Syndrome; OSTEITIS